Coal gangue-based bifunctional composite material, and preparation method and application thereof

CN122974265APending Publication Date: 2026-10-27NINGXIA INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611307433.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-27
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0006]针对现有技术中普遍存在的功能单一、固废资源化利用率低、复合废水处理效果差及制备成本高等问题,本发明提供一种煤矸石基双功能复合材料及其制备方法与应用

Benefits of technology

(1)本发明将活化煤矸石、铁钛双金属掺杂与石墨相氮化碳光催化改性三者有机结合,在同一材料体系中同时构建重金属吸附位点与可见光光催化降解位点,从而突破了传统煤矸石改性材料功能单一的局限,实现了复合废水中重金属离子与有机污染物的同步协同处理。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application discloses a coal gangue-based bifunctional composite material and a preparation method and application thereof, and belongs to the technical field of photocatalysis and adsorption materials. The application uses waste coal gangue as a base, removes impurities through acid pickling, and constructs a porous carrier structure through high-temperature pre-activation; anhydrous ethanol is used as a dispersion medium to uniformly load iron source, titanium source and melamine on the surface and inside of the pores of the coal gangue; through drying and air atmosphere caking, iron oxide and titanium dioxide active sites are generated at the same time, a local ammonia-rich microenvironment is formed by using ammonia gas released during caking, and graphite phase carbon nitride is in-situ synthesized, so that the coal gangue-based bifunctional composite material modified by iron-titanium co-doping and graphite phase carbon nitride compounding is prepared. The material has the functions of heavy metal adsorption and visible light catalytic degradation, can simultaneously remove Pb 2+ , Cd 2+ , Cr 6+ and other heavy metal ions and phenol and other organic pollutants in water, the removal rate of the heavy metal ions reaches 83% to 88%, the degradation and removal rate of the phenol reaches 82% to 87%, and the material has CO2 adsorption and capture potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of photocatalytic synergistic adsorption materials technology, specifically to a coal gangue-based bifunctional composite material, its preparation method, and its application. Background Technology

[0002] Coal gangue is a large-scale industrial solid waste generated during coal mining and washing, with massive and increasing stockpiles year by year. The long-term open-air storage of large quantities of coal gangue not only occupies land resources but also easily generates dust pollution. Furthermore, after being leached by rainwater, the sulfides and heavy metal ions within it seep into the soil and groundwater, posing a serious threat to the surrounding ecological environment. Therefore, the efficient and resource-based utilization of coal gangue has become an urgent problem to be solved.

[0003] Currently, the main ways to utilize coal gangue include backfilling in mining areas, road construction, and the production of building materials such as bricks and cement admixtures, resulting in low added value. In recent years, the use of coal gangue to prepare wastewater treatment adsorption materials has attracted widespread attention. However, most existing coal gangue modification technologies have limited functionality; some technologies only impart adsorption properties for heavy metal ions, while others only impart photocatalytic degradation properties for organic pollutants. These technologies cannot simultaneously address the common problem of combined heavy metal ion and organic pollutant pollution in industrial wastewater.

[0004] Furthermore, existing iron-titanium modified or graphitic carbon nitride composite materials mostly use pure chemical reagents as a base, resulting in high raw material costs and failing to fully utilize the natural porous structure and resource advantages of coal gangue. Traditional modification processes generally suffer from drawbacks such as single active sites, poor synergistic treatment effects, complex preparation processes, and high costs.

[0005] Therefore, developing a low-cost coal gangue-based material that can realize the resource utilization of solid waste and simultaneously achieve the adsorption of heavy metals and the photocatalytic degradation of organic pollutants has important engineering application value and environmental significance. Summary of the Invention

[0006] To address the common problems in existing technologies, such as single function, low utilization rate of solid waste resources, poor treatment effect of complex wastewater, and high preparation cost, this invention provides a coal gangue-based bifunctional composite material, its preparation method, and its application. This invention uses industrial solid waste coal gangue as a substrate, which undergoes acid washing and high-temperature activation treatment to construct a porous carrier structure. Anhydrous ethanol is used as the dispersion medium to effectively suppress the rapid hydrolysis and aggregation of tetrabutyl titanate upon contact with water, ensuring that the iron source, titanium source, and melamine precursor can be uniformly loaded on the surface and inside the pores of the coal gangue. Subsequently, through drying and air-atmosphere calcination with a cap, active sites for iron oxide and titanium dioxide are stably generated. Furthermore, the ammonia released during calcination creates a locally ammonia-rich microenvironment, allowing for the in-situ synthesis of highly stable graphitic carbon nitride (g-C3N4). The resulting composite material possesses both heavy metal adsorption and visible light photocatalytic degradation properties, enabling the simultaneous removal of heavy metal ions and organic pollutants from water, making it suitable for industrial complex wastewater treatment scenarios.

[0007] The technical solution provided by this invention is as follows: In a first aspect, the present invention provides a method for preparing a coal gangue-based bifunctional composite material, comprising the following steps: S1. The coal gangue is crushed, ball-milled, and sieved to obtain coal gangue powder. The coal gangue powder is then acid-washed to remove impurities, washed with deionized water, dried, and pre-activated at high temperature to obtain activated coal gangue powder. S2. Disperse the activated coal gangue powder obtained in step S1 in anhydrous ethanol, add iron source, titanium source and melamine, stir and mix to obtain composite suspension slurry; S3. Dry the composite suspension slurry obtained in step S2 to remove the anhydrous ethanol solvent and obtain the composite precursor powder. S4. The composite precursor powder obtained in step S3 is placed in a covered crucible, placed in a muffle furnace, and calcined in an air atmosphere to obtain a coal gangue-based bifunctional composite material.

[0008] Furthermore, in step S1, the sieving is performed through a 150-mesh standard sieve; the acid washing is performed using dilute hydrochloric acid for 2-3 hours; the high-temperature pre-activation temperature is 400-480℃, the heating rate is 3-8℃ / min, and the time is 1-2 hours.

[0009] Furthermore, in step S2, the iron source is ferric nitrate and the titanium source is tetrabutyl titanate.

[0010] Furthermore, in step S2, the mass-to-volume ratio of activated coal gangue powder to anhydrous ethanol is (0.08–0.15) g / mL; the mass ratio of iron source, titanium source, and melamine is 1:(1.2–1.8):(4–7).

[0011] Furthermore, in step S2, the mixing is carried out continuously at 40–60°C for 3–5 hours.

[0012] Furthermore, the drying temperature in step S3 is 100–110°C.

[0013] Furthermore, in step S4, the heating rate of calcination is 3–8 °C / min, the calcination temperature is 500–530 °C, and the time is 1–3 h.

[0014] Secondly, the present invention provides a coal gangue-based bifunctional composite material, which is prepared by any of the above-described methods for preparing a coal gangue-based bifunctional composite material.

[0015] Thirdly, the present invention provides the application of a coal gangue-based bifunctional composite material as described above in wastewater treatment.

[0016] Furthermore, it can be applied to the simultaneous removal of heavy metal ions and organic pollutants from water bodies.

[0017] The beneficial effects of this invention are as follows: (1) This invention organically combines activated coal gangue, iron-titanium bimetallic doping and graphite phase carbon nitride photocatalytic modification, and simultaneously constructs heavy metal adsorption sites and visible light photocatalytic degradation sites in the same material system, thereby breaking through the limitation of the single function of traditional coal gangue modified materials and realizing the synchronous synergistic treatment of heavy metal ions and organic pollutants in composite wastewater.

[0018] (2) This invention uses industrial solid waste coal gangue as the main raw material, realizing the resource utilization of waste. The raw material source is wide and the cost is low. It effectively solves the land occupation and environmental pollution problems caused by coal gangue stockpiling, and has both environmental and economic benefits.

[0019] (3) This invention opens up the closed channels of coal gangue through acid washing and high-temperature activation treatment, constructing a multi-level porous support structure; through iron-titanium co-doping, the material's complexation and adsorption capacity for heavy metal ions is significantly improved; and through in-situ composite with graphitic carbon nitride, the material is endowed with visible light photocatalytic activity. Under the synergistic effect of the three, the composite material has a high adsorption capacity for Pb. 2+ Cd 2+ Cr 6+ The removal rate of heavy metal ions can reach 83% to 88%, and the visible light photocatalytic degradation removal rate of organic pollutants such as phenol can reach 82% to 87%.

[0020] (4) The present invention uses conventional chemical equipment throughout the process, does not require inert gas protection, has mild process conditions, stable operation, strong repeatability, and is easy to achieve large-scale production. It can meet the actual needs of industrial composite wastewater pretreatment and deep treatment and has broad industrial application prospects.

[0021] (5) The composite material prepared by the present invention has a well-developed hierarchical porous structure. At the same time, the in-situ composite of graphite phase carbon nitride introduces a large number of basic nitrogen-containing functional groups, which provides abundant active sites for CO2 adsorption. Its CO2 saturated adsorption capacity can reach 0.32-0.43 mmol / g. Detailed Implementation

[0022] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only a part of the embodiments of this invention, not all of them. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention. Experimental methods in the following embodiments that do not specify specific conditions are generally performed under conventional conditions or as recommended by the manufacturer. Unless otherwise stated, percentages and parts are weight percentages and parts by weight.

[0023] Unless otherwise specified, the technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains. It should be noted that the terms used herein are for the purpose of describing particular embodiments only and are not intended to limit the exemplary embodiments of this application.

[0024] The technical solution of this invention is as follows: A method for preparing a coal gangue-based bifunctional composite material includes the following steps: S1. Preparation of activated coal gangue powder Waste coal gangue from the mining area was crushed, ball-milled, and then passed through a 150-mesh standard sieve to obtain coal gangue powder. The powder was then acid-washed with dilute hydrochloric acid at room temperature for 2–3 hours to remove carbonate impurities and soluble inert components. After acid washing, the powder was washed with deionized water until the filtrate was neutral, and then placed in an oven and dried at 100–110℃. The dried coal gangue powder was then placed in a muffle furnace and heated to 400–480℃ at a rate of 3–8℃ / min for high-temperature pre-activation for 1–2 hours. After the pre-activation, the powder was allowed to cool naturally to room temperature, resulting in activated coal gangue powder with a well-developed porous structure and higher surface activity. S2. Preparation of composite suspension slurry Using anhydrous ethanol as the sole dispersion medium, activated coal gangue powder was uniformly dispersed in anhydrous ethanol and continuously stirred to form a stable suspension system. First, an iron source was added to the suspension system and stirred thoroughly until uniformly dispersed. Then, a titanium source was slowly added dropwise, and the hydrolysis rate of the titanium source was controlled by the ethanol system to avoid instantaneous agglomeration and sedimentation of the titanium source. Finally, melamine was added, and the mixture was stirred continuously at a constant temperature of 40–60°C for 3–5 hours to allow the iron precursor, titanium precursor, and melamine precursor to fully wet all the pores of the coal gangue and uniformly adhere to the inner and outer surfaces of the particles, resulting in a composite suspension slurry with uniformly dispersed components. The iron source is ferric nitrate, and the titanium source is tetrabutyl titanate; the mass-to-volume ratio of activated coal gangue powder to anhydrous ethanol is (0.08–0.15) g / mL; the mass ratio of iron source, titanium source and melamine is 1:(1.2–1.8):(4–7).

[0025] S3. Preparation of composite precursor powder The composite suspension slurry was placed in an oven and dried at 100-110℃ to completely remove the anhydrous ethanol solvent. During the solvent evaporation process, various functional precursors were stably anchored on the porous framework of coal gangue without component loss or agglomeration, resulting in a composite precursor powder with uniform component distribution and complete structure. S4. Preparation of coal gangue-based bifunctional composite materials The composite precursor powder was loaded into an alumina crucible with a sealed lid, and the whole thing was placed in a muffle furnace and calcined in a static air atmosphere. The temperature was raised to 500-530°C at a heating rate of 3-8°C / min, and calcined at a constant temperature for 1-3 hours. After calcination, it was naturally cooled to room temperature. During the calcination process, the iron precursor thermally decomposes to generate iron oxide active components, the titanium precursor undergoes decrystallization to form titanium dioxide active sites, and melamine undergoes thermal condensation and deamination reaction to generate graphitic carbon nitride (g-C3N4) in situ. At the same time, the ammonia gas released from the reaction is retained in the sealed space of the crucible, forming a locally ammonia-rich microenvironment, which effectively inhibits the oxidation and decomposition of carbon nitride under high temperature conditions, and finally obtains iron-titanium co-doped and g-C3N4 composite modified coal gangue-based bifunctional composite material.

[0026] The coal gangue-based bifunctional composite material provided by this invention uses a multi-level porous framework constructed from activated coal gangue as a carrier, utilizing its rich pore structure to provide sufficient adsorption sites for heavy metal ions; at the same time, the in-situ supported iron-titanium oxides are coupled with graphitic carbon nitride to form a stable heterojunction photocatalytic system, enabling the material to have both heavy metal adsorption performance and visible light photocatalytic degradation performance, achieving synergistic integration of the two.

[0027] The present invention will be further described below with reference to specific embodiments. Example

[0028] This embodiment provides a method for preparing a coal gangue-based bifunctional composite material, including the following steps: S1. Preparation of activated coal gangue powder Waste coal gangue from the mining area was crushed, ball-milled, and then passed through a 150-mesh standard sieve to obtain coal gangue powder. The powder was then acid-washed with dilute hydrochloric acid at room temperature for 2.5 hours to remove carbonate impurities and soluble inert components. After acid washing, the powder was washed with deionized water until the filtrate was neutral, and then placed in an oven and dried at 105℃. The dried coal gangue powder was then placed in a muffle furnace and heated to 440℃ at a rate of 5℃ / min for high-temperature pre-activation for 1.5 hours. After activation, the powder was allowed to cool naturally to room temperature, resulting in activated coal gangue powder with a well-developed porous structure and higher surface activity. S2. Preparation of composite suspension slurry Using anhydrous ethanol as the sole dispersion medium, 10g of activated coal gangue powder was uniformly dispersed in 100mL of anhydrous ethanol and continuously stirred to form a stable suspension system. First, 2g of ferric nitrate was added to the suspension system and stirred thoroughly until uniformly dispersed. Then, 3g of tetrabutyl titanate was slowly added dropwise, and finally 11g of melamine was added. The mixture was continuously stirred at 50℃ for 4 hours to obtain a composite suspension slurry with uniformly dispersed components. S3: Preparation of composite precursor powder. The composite suspension slurry was placed in an oven and dried at a constant temperature of 105℃ to completely remove the anhydrous ethanol solvent, thus obtaining the composite precursor powder. S4. Preparation of coal gangue-based bifunctional composite materials The composite precursor powder was loaded into an alumina crucible with a sealed lid, and the whole thing was placed in a muffle furnace and calcined in a static air atmosphere. The temperature was raised to 520°C at a heating rate of 5°C / min and calcined at a constant temperature for 2 hours. After calcination, it was naturally cooled to room temperature to obtain a coal gangue-based bifunctional composite material.

[0029] Performance testing The heavy metal adsorption performance and photocatalytic degradation performance of the coal gangue-based bifunctional composite material prepared in Example 1 were tested.

[0030] 1. Adsorption performance of heavy metal ions in water Under normal temperature and pH 6–8 aquatic conditions, preparations containing single Pb were formulated respectively. 2+ Single Cd 2+ Single Cr 6+ Simulated wastewater was prepared, and the pH of the wastewater was adjusted to 6-8 using dilute nitric acid or sodium hydroxide solution. The composite material was then added to the simulated wastewater at a rate of 2.0 g per liter, and a static adsorption experiment was conducted under light-protected conditions with continuous stirring. After adsorption equilibrium was reached, samples were taken and filtered. The concentration of residual heavy metal ions in the filtrate was determined spectrophotometrically, and the removal rate of heavy metal ions was calculated.

[0031] Table 1. Removal rates of different heavy metal ions by composite materials

[0032] Test results show that this composite material has good adhesion to Pb in water. 2+ Cd 2+ Cr 6+ The average removal rate can reach 83% to 88%, demonstrating excellent heavy metal ion adsorption performance.

[0033] 2. Photocatalytic degradation performance of organic pollutants Phenol aqueous solution was selected as the organic simulated pollutant. The composite material was added to it at a rate of 2.0 g per liter of organic simulated pollutant. The mixture was stirred for 30 min under light-protected conditions to reach adsorption-desorption equilibrium. Then, a visible light source was turned on and the mixture was continuously irradiated for 120 min. Samples were taken at regular intervals during the irradiation period. After filtration, the concentration of residual phenol in the filtrate was determined using a UV-Vis spectrophotometer, and the degradation and removal rate of the organic pollutant was calculated.

[0034] Table 2. Visible photocatalytic degradation removal rate of phenol by composite materials

[0035] Test results show that under visible light irradiation, the composite material can achieve a phenol degradation and removal rate of 82% to 87%, demonstrating good ability to degrade organic pollutants by visible light catalysis.

[0036] 3. CO2 adsorption performance The composite material has a well-developed hierarchical porous structure, and the graphite phase carbon nitride introduces a large number of basic nitrogen-containing functional groups in situ, providing abundant active sites for CO2 adsorption.

[0037] After the composite material was fully dried, it was placed in a sealed reaction vessel and subjected to a static adsorption test by introducing high-purity CO2 under constant temperature and atmospheric pressure conditions of 25°C. After the adsorption equilibrium was reached, the change in CO2 concentration in the system was detected by gas chromatography, and the CO2 saturated adsorption capacity of the material was calculated.

[0038] Test results show that the saturated adsorption capacity of the composite material for CO2 can reach 0.32–0.43 mmol / g, indicating that it has good CO2 adsorption and capture potential.

[0039] In summary, this invention uses coal gangue as a substrate. First, it removes carbonate impurities and soluble inert components through acid washing. Then, a multi-level porous carrier structure is constructed through high-temperature pre-activation. Subsequently, using anhydrous ethanol as a dispersion medium, iron, titanium, and melamine precursors are uniformly loaded onto the carrier surface and inside the pores. After calcination in an air atmosphere, a coal gangue-based bifunctional composite material modified with iron-titanium co-doping and graphite-phase carbon nitride was successfully prepared. This material fully utilizes the natural porous structure of coal gangue, realizing the resource utilization of solid waste. It possesses both heavy metal adsorption and visible light photocatalytic degradation functions, and can simultaneously remove Pb from water. 2+ Cd 2+ Cr 6+ It contains heavy metal ions and organic pollutants such as phenol, and also shows potential for CO2 adsorption and capture.

[0040] The above descriptions are merely embodiments of the present invention, and common knowledge such as specific technical solutions and / or characteristics are not described in detail here. It should be noted that those skilled in the art can make various modifications and improvements without departing from the technical solutions of the present invention, and these should also be considered within the scope of protection of the present invention. These modifications and improvements will not affect the effectiveness of the implementation of the present invention or the practicality of the patent. The scope of protection claimed in this application should be determined by the content of its claims, and the specific embodiments described in the specification can be used to interpret the content of the claims.

Claims

1. A method for preparing a coal gangue-based bifunctional composite material, characterized in that, Includes the following steps: S1. The coal gangue is crushed, ball-milled, and sieved to obtain coal gangue powder. The coal gangue powder is then acid-washed to remove impurities, washed with deionized water, dried, and pre-activated at high temperature to obtain activated coal gangue powder. S2. Disperse the activated coal gangue powder obtained in step S1 in anhydrous ethanol, add iron source, titanium source and melamine, stir and mix to obtain composite suspension slurry; S3. Dry the composite suspension slurry obtained in step S2 to remove the anhydrous ethanol solvent and obtain the composite precursor powder. S4. The composite precursor powder obtained in step S3 is placed in a covered crucible, placed in a muffle furnace, and calcined in an air atmosphere to obtain a coal gangue-based bifunctional composite material.

2. The method for preparing a coal gangue-based bifunctional composite material according to claim 1, characterized in that, In step S1, the sieving is performed through a 150-mesh standard sieve; the acid washing is performed using dilute hydrochloric acid for 2-3 hours; the high-temperature pre-activation temperature is 400-480℃, the heating rate is 3-8℃ / min, and the time is 1-2 hours.

3. The method for preparing a coal gangue-based bifunctional composite material according to claim 1, characterized in that, In step S2, the iron source is ferric nitrate and the titanium source is tetrabutyl titanate.

4. The method for preparing a coal gangue-based bifunctional composite material according to claim 1, characterized in that, In step S2, the mass-to-volume ratio of activated coal gangue powder to anhydrous ethanol is (0.08–0.15) g / mL; the mass ratio of iron source, titanium source and melamine is 1:(1.2–1.8):(4–7).

5. The method for preparing a coal gangue-based bifunctional composite material according to claim 1, characterized in that, In step S2, the mixing is carried out by stirring continuously at 40–60°C for 3–5 hours.

6. The method for preparing a coal gangue-based bifunctional composite material according to claim 1, characterized in that, The drying temperature in step S3 is 100-110℃.

7. The method for preparing a coal gangue-based bifunctional composite material according to claim 1, characterized in that, In step S4, the heating rate of calcination is 3-8℃ / min, the calcination temperature is 500-530℃, and the time is 1-3h.

8. A coal gangue-based bifunctional composite material, characterized in that, The composite material is prepared by the method described in any one of claims 1-7.

9. The application of the coal gangue-based bifunctional composite material as described in claim 8 in wastewater treatment.

10. The application according to claim 9, characterized in that, The application is to simultaneously remove heavy metal ions and organic pollutants from water bodies.